AN ANALYSIS ON THE IMPLEMENTATION OF ROLE PLAY IN TEACHING SPEAKING - Rekhavitri, Rengganis; Manurung, Konder; Hasyim, Zarkiani; Mukrim, Mukrim (Tadulako University, 2024)
Speaking is one of the most important skills to be developed in order to communicate effectively. Therefore, the goal of teaching speaking skills is communicative efficiency. In order to achieve the goal, many methods and techniques are applied including role play method. This research aims to analyze how to implement role play in teaching speaking English based on the previous research. This study applied a library research, which is part of qualitative research. Data were collected through undergraduate thesis, thesis, and journal articles published in 2014 to 2023. The data were analyzed using content analysis based on Harmer (2007). There are ten scientific writings from Susilo (2014), Hidayanti (2015), Sholikah (2017), Agustiningrum (2019), Sholiha (2020), Tumada et al. (2020), Marwa (2020), Arifin (2021), Farisya (2022), and Magfirah (2022). Some researchers refer to expert recommendations using role play by Harmer (2007), Lewin (1990), and Kemmis and Mc Taggart (1988) procedure. The results of the study show that the implementation of role play is effective in improving students speaking skills because students take a new identity and learn to use a foreign language students for every day interaction. Besides that, role play technique is ineffective in teaching speaking skills because of some factors for some students and teacher. Students and teachers using the role play technique to develop and teach speaking skills should prioritize preparation, participation, and reflection. To get the most out of the learning experience, students should actively participate in the scenarios, taking on their roles with excitement and originality. They should also be receptive to comments and willing to practice frequently in order to enhance their fluency and confidence. Teachers should carefully select or create role play scenarios that are both relevant and demanding, with clear directions and enough support.